Fiscal Federalism in Nepal: Challenges and Opportunities - Shah, R. K. (Research Nepal Journal of Development Studies, 2019)
The Constitution of Nepal was formally promulgated and it declared the country as a Federal Democratic Republic on September 20, 2015 by the Second CA. Fiscal powers were shared among the federal government, the state governments and the local governments. The Constitution further defined the framework of fiscal federalism within the pattern of income and resource distribution. The primary objectives of this study is to review the modality presented in the new Constitution on the natural resources, economic rights and revenue allocation. The study finds that the fiscal decentralization initiatives have not been successful in minimizing the political, social, economic, regional and ethnic inequalities inherent for nearly 240 years of a unitary system of governance in Nepal. The study recommends that VAT, excise duties and income taxes have to be allocated at the federal, states and local levels in the ratio of 70 percent, 15 percent and 15 percent respectively by the Constitution. Intergovernmental transfer modality has included in the Constitution. Revenue sharing from hydropower has been a controversial issue in Nepal. National Natural Resources and Fiscal Commission (NNRFC) has been constituted at the central level to make national level development plans and to make recommendations for additional grants and loans for the state and local governments. The Constitution has further defined the framework of fiscal federalism within the pattern of income and resource distribution. The theoretical study indicates that there is various controversial and overlapping issues required clarity in process of implementation in the years to come.